1985
DOI: 10.1029/ja090ia09p08433
|View full text |Cite
|
Sign up to set email alerts
|

A Safari‐Eiscat comparison between the velocity of F region small‐scale irregularities and the ion drift

Abstract: Simultaneous data were obtained bet-Various kinds of ground-based facilities also proween the SAFARI HF coherent radars and the EISCAT vide an access to the ionospheric electric field. incoherent scatter experiment in December 1953. Incoherent scatter radars measure most parameters

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
79
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 25 publications
1
79
0
Order By: Relevance
“…The use of HF frequencies meant that the SuperDARN radars measured the Doppler velocity of F-region irregularity backscatter targets moving with the ambient plasma at the E Â B convection velocity (Ossakow and Chataverdi 1979;Tsunoda 1988). The equivalence of these velocities was first shown for HF radar backscatter by Villain et al (1985) and later by Ruohoniemi et al (1987) using Goose Bay data. Further larger-scale statistical studies using other Super-DARN radars confirmed this relationship (Davies et al 1999Milan et al 1999a;Xu et al 2001;Drayton et al 2005).…”
Section: Measuring Global Convectionmentioning
confidence: 99%
“…The use of HF frequencies meant that the SuperDARN radars measured the Doppler velocity of F-region irregularity backscatter targets moving with the ambient plasma at the E Â B convection velocity (Ossakow and Chataverdi 1979;Tsunoda 1988). The equivalence of these velocities was first shown for HF radar backscatter by Villain et al (1985) and later by Ruohoniemi et al (1987) using Goose Bay data. Further larger-scale statistical studies using other Super-DARN radars confirmed this relationship (Davies et al 1999Milan et al 1999a;Xu et al 2001;Drayton et al 2005).…”
Section: Measuring Global Convectionmentioning
confidence: 99%
“…In this case, the velocity measured by the radar should be a true indication of the line-of-sight component of the plasma drift velocity V EÂB (Villain et al, 1985;Ruohoniemi et al, 1987). It is interesting to note that at¯ow angles outside the cone of instability of the two-stream instability (i.e.…”
Section: Instability Mechanismsmentioning
confidence: 99%
“…Such structures provide steep electron density gradients in which smaller-scale irregularities can grow. Previous studies indicate that F-region irregularities observed by HF radars propagate with the plasma drift speed, V EÂB , and are not velocity limited (Villain et al, 1985;Ruohoniemi et al, 1987), making them suitable tracers of the plasmā ow.…”
Section: Introductionmentioning
confidence: 99%
“…In the high-latitude ionosphere, these ionospheric irregularities are often present (Tsunoda, 1988). The irregularities move with the background plasma drift at F-region altitudes (Villain et al, 1985;Ruohoniemi et al, 1987) and so provide information about large-scale convection-related processes in the radar ®eld-of-view. The SuperDARN radars are therefore a very good diagnostic tool for studies of magnetosphereionosphere coupling.…”
Section: Instrumentationmentioning
confidence: 99%